Pendugaan nilai heritabilitas sifat pertumbuhan pada Sapi Madura - Yuli Arif Tribudi; V. M. Ani Nurgiartiningsih; Peni W. Prihandini (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2019)
Madura, a local cattle breed in Indonesia,  is included as a national genetic resource. Genetic evaluation for growth traits in Madura cattle is important for appropriate utilization and improvement of this breed. The aim of this study was to estimate the heritability for growth traits in Madura cattle. The method used in this study is a data recording from 2010 until 2016 including birth weight (190 animals), weight at day 205 (155 animals) and weight at day 365 (135 animals) were used for heritability estimates by using paternal half sib correlation. The results showed that heritability estimates for birth weight, weight at day 205 and weight at day 365 were 0.38±0.17; 0.64±0.22 dan 0.54±0.18. Estimates of heritability for growth traits in Madura cattle ranged between medium and high. In conclusion,growth traits can be used as selection criteria for future genetic improvement in Madura cattle.